Plastik nonwoven sebagai pengemas bahan makanan yang bersifat breathable - Setyowati, Penny (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 2003)
Nonwoven plastic is a new material for packagingÂ that has some special quality among the other things such as flexible, higher strength, hydrophob, breathable and hygienes. The technology of nonwoven plastic is spunbond technolog which is a clean technology and produce a non fibre product. The raw material of nonwoven plastic is food grade polypropylene, so that the products are safe for food packaging. Recently just pioneered of nonwoven plastic application as innerliner of plastic sack that can replace âkarung goniâas rice packaging and replace cotton sack as meal or flour packaging. ThereforeÂ grains that have not been prepared yet, respiration activity is very important to be breathable characteristic of nonwoven plastic is able to support air circulation very well and also to keep humidity balance in the packaging. At the flour packaging, beside hydrophob characteristic, however breathable characteristic is necessary too because flourÂ has a tendency to absorb water and flour stability must be kept at 13.5 â 14% moisture content. The first experiment was taken by PT. Boma Internusa concerning with rice storage that use nonwoven plastic packaging as innerliner of plastic sack during 2 months, and analysis showed that the rice did not smell, louse unfolding was decrease 9fumigation cost was low), yellow grains and broken grains were decrease and did not occur any change of color. In the experiment of flour storage during 3 months gave an analysis that flour wsa still having good condition and fulfilled the standard trade.Â Keywords: Nonwoven, food packaging, plastic.Â